A 2004 Social Accounting Matrix for Israel: Documentation of an Economy-Wide Database with a Focus on Agriculture, the Labour Market, and Income Distribution - Khalid Hassan Ali Siddig; Dorothee Flaig; Jonas Jens Luckmann; Harald Grethe (Universität Hohenheim, Institut für Agrarpolitik und Landwirtschaftliche Marktlehre, 2011)
This document describes the Israeli Social Accounting Matrix (SAM) for the year 2004, developed by the Agricultural and Food Policy Group at the University of Hohenheim. The SAM is a part of a larger research project which aims to analyse several economic, trade, and labour policies in the context of economic integration of agriculture between Israel and the West Bank. Data are obtained from various sources in Israel. Sources include the Israeli Central Bureau of Statistics (ICBS), the Central Bank of Israel (CBI), and the Israeli Tax Authority (ITA). Data from sources outside of Israel are used to fill-in some gaps in the domestic reports. External sources include the World Trade Organization (WTO), the Organisation for Economic Co-operation and Development (OECD), and the World Bank. The SAM provides data on 47 sectors with activities separated from commodities, 36 labour force types, 10 household groups, as well as 17 tax accounts in addition to 37 accounts reserved for taxes on production factors. A topdown approach is pursued by first building a balanced macro SAM which is consistent with 2004 national account data. Subsequently, the macro SAM is disaggregated into a micro SAM which is balanced in several steps. – – Dieser Bericht beschreibt die "Social Accounting Matrix" (SAM) für Israel für das Jahr 2004, welche am Fachgebiet für Agrar- und Ernährungspolitik der Universität Hohenheim erstellt wurde. Die israelische SAM ist Teil eines größeren Forschungsprojektes mit dem Ziel verschiedene ökonomische, Handels- und Arbeitsmarktpolitiken im Kontext der ökonomischen Integration von landwirtschaftlichen Märkten zwischen Israel und dem Westjordanland zu analysieren. Es werden Daten von verschiedenen israelischen Quellen verwandt: dem israelischen statistischem Amt (ICBS), der israelischen Zentralbank (BOI) und der israelischen Steuerbehörde (ITA). Diese werde durch nicht-israelische Quellen ergänzt, welche die Welthandelsorganisation (WTO), die Organisation für wirtschaftliche Zusammenarbeit und Entwicklung (OECD), sowie die Weltbank umfassen. Die SAM differenziert 47 Sektoren, wobei Aktivitäten und Güter unterschieden werden. Ferner beinhaltet die SAM 36 Klassen des Produktionsfaktors Arbeit und 10 unterschiedliche Haushaltsgruppen, die durch 54 verschiedene Steuern (davon 37 auf Produktionsfaktoren) ergänzt werden. Die Erstellung der SAM erfolgt folgendermaßen: zuerst wird eine mit den israelischen volkswirtschaftlichen Daten für 2004 konsistente Makro-SAM erstellt. Diese wird im nächsten Schritt disaggregiert in eine detaillierte Mikro-SAM, welche in mehreren Stufen ausbalanciert wird.
urn:nbn:de:bsz:100-opus-6251
Keywords: C6; C8 D1; D3; D5; D6; E2; E6; F1; F2; H2; 330; SAM; IO-Table; CGE; Database; Social-accounting-Matrix; Input-Output-Tabelle; Datenbank; Israel; Sozialrechnungsmatrix; Israel